ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI SAHAM (Students' Journal of Accounting and Banking, 2012)
This study aimed to investigate the factors - fundamental factors that can affect the value of the stock at a manufacturing company in the Stock Exchange Indonesia. Factors - factors that influence the independent variables include the Debt to Equity Ratio (DER), Return on Equity (ROE) and Earning per Share (EPS). While the value of company stock as dependent variable was measured by Price Earning Ratio (PER).In this study obtained a sample of 128 companies. sampling with purposive sampling method. While the methods of analysis used the multiple regression analysis. The results showed that the variable Debt to Equity Ratio (DER), Return on Equity (ROE) and Earning per Share (EPS) have a significant negative effect on Price Earning Ratio either simultaneously or partially.Keywords: Price Earning Ratio (PER), Debt to Equity Ratio (DER), Return on Equity (ROE) and Earning per Share (EPS).